Zinc oxide family semiconductors for ultraviolet radiation emission – A cathodoluminescence study. (September 2022) - Chaudhari, Ashok; Cui, Xin; Hoex, Bram; Hyde, Lachlan; Ironside, Charlie N.; Jadwisienczak, Wojciech M.; Kordesch, Martin E.; Rahman, Faiz; Vispute, R.D.
Highlights: Study of ZnO and MgZnO grown using a variety of techniques. UV cathodoluminescence seen in bulk ZnO and in epitaxial MgZnO. Sputtered MgZnO shows no UV cathodoluminescence. Atomic layer deposition appears to be suitable for growing UV-luminescent MgZnO films. ABSTRACT: Zinc oxide (ZnO) family semiconductors that include ZnO and various ternary and even quaternary semiconductors formed by the inclusion of suitable other elements to zinc and oxygen are potential candidates for making UV-emitting solid-state devices. This work is a study of the UV-emitting potential of ZnO and MgZnO through electron beam irradiation of various samples. In this work, we studied materials grown or deposited through different techniques in order to assess their suitability for use in UV-emitting devices. Our work throws light on which growth or deposition methods are more suitable for obtaining radiation emission-capable materials from this family of II-VI oxide semiconductors. We find that single crystal thin film material, produced through either metal organic chemical vapor deposition (MOCVD) or atomic layer deposition (ALD) appear to be the best, followed by hydrothermally-grown single crystals. In contrast, sputtered material appears unsuitable for making UV-emitting devices. Graphical Abstract: Image, graphical abstract